Meningkatkan Keterampilan Komunikasi dan Motivasi Menggunakan Model Barasih dan Media Kahoot di SDN Telawang 3 Banjarmasin - Aina, Aina; Pratiwi, Diani Ayu (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
The problem in this research is the low communication skills and learning motivation of students caused by the lack of communicative activities such as questions and answers and group discussions. Then learning is also monotonous and less enjoyable. One of the efforts made is through the use of the Barasih learning model (Problem Based Learning, Think Pair Share, and Course Review Horay) and the Kahoot application media. The aim of this research is to improve students' communication skills and learning motivation. This research uses the type of Classroom Action Research (PTK). The research subjects were 25 class IVB students at SDN Telawang 3 Banjarmasin for the 2023/2024 academic year. The types of data in this research are qualitative data obtained from observing communication skills, observing motivation and motivation questionnaires. The research results showed that the students' communication skills at the 1st to 4th meetings increased from the criteria of "Quite Skilled" to "Very Skilled". Students' learning motivation as seen from observations increased at the 1st to 4th meetings from "Low" to "Very High" criteria. Students' learning motivation taken from the questionnaire increased at the 1st to 4th meeting from the "Low" criteria to "Very High". It can be concluded that the Barasih model and Kahoot media can improve student’s communication skills and learning motivation.